2021
DOI: 10.21203/rs.3.rs-258956/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Culture-dependent and Universal Constructs and Promoting Factors for the Process of Personal Recovery in users of Mental Health Services: Qualitative Findings from Japan

Abstract: Background: The conceptualization of personal recovery began in Europe and North America and has spread worldwide. The concept of personal recovery and recovery-promoting factors may be influenced by culture. We explored how users of mental health services in Japan perceive their own personal recovery and the factors that promote it.Methods: We conducted semi-structured interviews and focus group interviews with individuals using mental health services. The interview data underwent thematic analysis, and we ad… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…43 On the other hand, in a subsequent qualitative study, they found that connections with others and freedom from social norms, which are unique to Japanese, are important for recovery. 44…”
Section: Qualitativementioning
confidence: 99%
See 2 more Smart Citations
“…43 On the other hand, in a subsequent qualitative study, they found that connections with others and freedom from social norms, which are unique to Japanese, are important for recovery. 44…”
Section: Qualitativementioning
confidence: 99%
“…Kanehara et al showed that the concept of personal recovery is generally applicable to the Japanese 43 . On the other hand, in a subsequent qualitative study, they found that connections with others and freedom from social norms, which are unique to Japanese, are important for recovery 44 …”
Section: How Can Values Be Measured/assessed?mentioning
confidence: 99%
See 1 more Smart Citation